2013
DOI: 10.1063/1.4827201
|View full text |Cite
|
Sign up to set email alerts
|

Fixed charge and trap states of in situ Al2O3 on Ga-face GaN metal-oxide-semiconductor capacitors grown by metalorganic chemical vapor deposition

Abstract: Articles you may be interested inNitride passivation reduces interfacial traps in atomic-layer-deposited Al2O3/GaAs (001) metal-oxidesemiconductor capacitors using atmospheric metal-organic chemical vapor deposition Appl. Phys. Lett. 105, 033513 (2014); 10.1063/1.4891431 In-situ metalorganic chemical vapor deposition and capacitance-voltage characterizations of Al2O3 on Ga-face GaN metal-oxide-semiconductor capacitors Appl. Phys. Lett. 103, 053509 (2013); 10.1063/1.4817385Bulk and interface trapping in the gat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 13 publications
(48 reference statements)
0
17
0
Order By: Relevance
“…Choi et al 35 using the first principles calculations showed that C Al can produce traps near/at the Al 2 O 3 /III-nitride interface. Based on these results as well as on the comparative electrical and photoelectric studies, Liu et al 36 suggested that the slow interface states at Al 2 O 3 /GaN interfaces originate from C impurities. Furthermore, Jackson et al 37 using the capacitance deep level optical spectroscopy claimed that D it (E) near VB at Al 2 O 3 /GaN interface is due to residual C atoms from nucleation of the ALD process.…”
Section: A Properties Of D It (E)mentioning
confidence: 99%
See 1 more Smart Citation
“…Choi et al 35 using the first principles calculations showed that C Al can produce traps near/at the Al 2 O 3 /III-nitride interface. Based on these results as well as on the comparative electrical and photoelectric studies, Liu et al 36 suggested that the slow interface states at Al 2 O 3 /GaN interfaces originate from C impurities. Furthermore, Jackson et al 37 using the capacitance deep level optical spectroscopy claimed that D it (E) near VB at Al 2 O 3 /GaN interface is due to residual C atoms from nucleation of the ALD process.…”
Section: A Properties Of D It (E)mentioning
confidence: 99%
“…According to some reports, [35][36][37] the origin of interface states at oxide/III-N interfaces can be related to C impurities near/at the interface. Choi et al 35 using the first principles calculations showed that C Al can produce traps near/at the Al 2 O 3 /III-nitride interface.…”
Section: A Properties Of D It (E)mentioning
confidence: 99%
“…The value of Q trapped extracted from Δ V FB is found to be 5.1 ± 0.4 × 10 10 cm −2 in all the samples. Note that V FB exhibits a linear relationship with ZrO 2 layer thickness, which along with a constant value of Q trapped provides further evidence that the trapped charge is primarily localized as a line charge (in units of cm −2 ) at or near the ZrO 2 /GaN interface . The aforementioned results confirm that no new slow trap states are generated at a large thickness of the ZrO 2 layer.…”
Section: A Summary Of Schottky Junction Parameters Estimated Using Thmentioning
confidence: 99%
“…Note that for fully compensated surface polarization charge by N DS , the net charge N int tends to be close to zero. [7][8][9]14 D it distribution was determined on MOS-HEMT structures with t ox ¼ 10 nm only, as it is expected to be independent of t ox . Two complementary techniques were used: (1) D it in the energy range of E C -E ¼ 0.5-1.0 eV was determined using V th -transients, deduced from the capacitance transients measured at V g %V th À0.5 V at temperatures of 25, 75, and 125 C. Only relative change (DV th ) between V th transients measured after "filling" pulse V F ¼ 0 (no filling) and V F ¼ 1.5 V (interface traps filling) was used for D it determination, to cancel out possible bulk trapping process (i.e., V th drift) previously discussed in Ref.…”
Section: Methodsmentioning
confidence: 99%